High prevalence of human polyomavirus JC VP1 gene sequences in pediatric malignancies - Shiramizu, B.; Hu, N.; Frisque, R.; Nerurkar, V. (Cellular and Molecular Biology, 2007)
The oncogenic potential of human polyomavirus JC (JCV), a ubiquitous virus that establishes infection during early childhood in approximately 70% of the human population, is unclear. As a neurotropic virus, JCV has been implicated in pediatric central nervous system tumors and has been suggested to be a pathogenic agent in pediatric acute lymphoblastic leukemia. Recent studies have demonstrated JCV gene sequences in pediatric medulloblastomas and among patients with colorectal cancer. JCV early protein T-antigen (TAg) can form complexes with cellular regulatory proteins and thus may play a role in tumorigenesis. Since JCV is detected in B-lymphocytes, a retrospective analysis of pediatric B-cell and non-B-cell malignancies as well as other HIV-associated pediatric malignancies was conducted for the presence of JCV gene sequences. DNA was extracted from 49 pediatric malignancies, including Hodgkin disease, non-Hodgkin lymphoma, large cell lymphoma and sarcoma. Polymerase chain reaction (PCR) was conducted using JCV specific nested primer sets for the transcriptional control region (TCR), TAg, and viral capsid protein 1 (VP1) genes. Southern blot analysis and DNA sequencing were used to confirm specificity of the amplicons. A 215-bp region of the JCV VP1 gene was amplified from 26 (53%) pediatric tumor tissues. The JCV TCR and two JCV gene regions were amplified from a leiomyosarcoma specimen from an HIV-infected patient. The leiomyosarcoma specimen from the cecum harbored the archetype strain of JCV. Including the leiomyosarcoma specimen, three of five specimens sequenced were typed as JCV genotype 2. The failure to amplify JCV TCR, and TAg gene sequences in the presence of JCV VP1 gene sequence is surprising. Even though JCV TAg gene, which is similar to the SV40 TAg gene, is oncogenic in animal models, the presence of JCV gene sequences in pediatric malignancies does not prove causality. In light of the available data on the presence of JCV in normal and cancerous colon epithelial tissue and our data on amplification of JCV from the cecum of an HIV-infected pediatric patient, further studies are warranted on the role of colon epithelium in the pathogenesis of JCV infection.